Realising creativity in management education: Putting student energy into action. Issue 2 (July 2019) - Sunley, Roz; Harding, Lisa; Jones, Josh
Abstract: This paper discusses how creative design in first year undergraduate management education can encourage student engagement in learning. In today's landscape of educational consumerism, educators have to decide whether to offer students what they say they want, or what professional wisdom suggests they actually need. Discussion includes the challenges of creative practice for both students and academic staff, and considers theoretical perspectives that influence the intentional design of a 12 week academic and professional skills course. The paper includes personal narrative from a first year student who encountered the creativity, peer coaching, personal reading, community engagement and self-reflection elements of this approach; and who exemplifies the evolving attitudes of many students to the course. Suggestions are offered on how to manage students' changing expectations and academic resistance to change, while valuing the professional wisdom that underpins pedagogic innovation; and some potential implications for practice and research. Highlights: Creative skills are becoming increasingly valued in a changing workplace. Creativity within intentional curriculum design encourages student engagement. Creativity encourages the use of different processes of cognition. Creative discomfort can help students better understand themselves as learners.